Visco-elastic fluid model in an inclined porous stenosed artery with slip effect and body acceleration - Manisha, Rana; Kumar, Surendra (Zielona Góra: Uniwersytet Zielonogórski)
The present paper analyzes an unsteady magnetohydrodynamic blood flow model of an visco-elastic fluid through an inclined porous stenosed artery with body acceleration and slip effect. Navier-Stokes equations have been used to describe the blood flow model. The governing equation of blood flow is solved by an analytic method by considering blood as an incompressible, visco-elastic fluid, and suspension of RBC`s in plasma.
Keywords: visco-elastic fluid; slip condition; inclined porous artery; permeability; body acceleration